Inovasi Pembelajaran Matematika Berbasis Android untuk Materi Operasi Hitung Bilangan Bulat di SD/MI (Studi Kasus SDN 45 Mataram) - Nurullaela, Nurlaela (Universitas Muhammadiyah Mataram, 2025)
This research aimed to develop an Android-based learning media for teaching integer arithmetic operations to elementary and primary school (SD/MI) students. The study employed a research and development (R&D) approach, adopting the model proposed by Hoge, Tondora, and Marrelli, which consists of seven systematic stages: (1) Defining Objectives, including a thorough needs analysis and goal setting for the learning media; (2) Securing Technical Support, which involved selecting appropriate software, including Canva, iSpring Suite 10, and Website 2 APK, to convert the media into an Android-compatible format; (3) Developing and Implementing Communication and Education Plans, ensuring collaboration with media and subject matter experts to align content with educational standards; (4) Planning the Methodology, including storyboard creation, material selection, and interface design; (5) Identifying and Creating the Model, building and refining prototypes based on expert feedback; (6) Applying the Model, conducting small and large group trials to evaluate effectiveness and user experience; and (7) Evaluating and Refining the Model, improving the media based on user feedback and performance data. The study was conducted at SD Negeri 45 Mataram during the first semester of the 2024/2025 academic year, involving first and fourth-grade students. Data were collected through observations, questionnaires, interviews, and documentation, with both qualitative and quantitative analysis. The results indicated that the developed learning media received high ratings across multiple aspects: content quality (average score 4.6, categorized as 'Excellent'), media design (average score 4.5, 'Excellent'), and technical functionality (average score 4.7, 'Excellent'). Small group trials with 10 students yielded an average feasibility score of 89.5%, while large group trials with 20 students reached 91.75%, both categorized as 'Highly Feasible'. These findings suggest that the developed Android-based learning media is highly effective in enhancing student motivation, understanding, and engagement in mathematics learning, making it a valuable tool for elementary education.